Halogen bonds with coordinative nature: halogen bonding in a S–I+–S iodonium complex. Issue 6 (30th October 2014) - Koskinen, L.; Hirva, P.; Kalenius, E.; Jääskeläinen, S.; Rissanen, K.; Haukka, M.
Abstract : A thorough characterization of unusually strong I + –S halogen bonds indicates that halogen bonding is not merely an electrostatic contact but also has a strong coordinative nature, thus expanding the scope of halogen bonding. Abstract : A detailed study of unexpectedly strong iodonium–sulfur halogen bonds in [I(2-imidazolidinethione)2 ] + is presented. The interactions are characterized by single-crystal X-ray diffraction, charge density analysis based on QTAIM calculations, mass spectrometry, and NMR spectroscopy. The results, small R IS = 0.7 and high interaction energy of −60 kJ mol −1, support a coordinative nature of the halogen bond between the iodonium ion and the sp 2 hybridized sulfur atoms.